Untangling the Evolution of American Wild Grapes: Admixed Species and How to Find Them - Zecca, Giovanni; Labra, Massimo; Grassi, Fabrizio (Frontiers in Plant Science, 2020)
Natural hybridization and introgression are central evolutionary processes in grape genus (Vitis). On the other hand, the interspecific relationships among grapes, the directionality of the inferred admixture events and the parents of hybrids are not yet completely clarified. The grapes are economically important crops characterized by tendrils used to climb on the trees and the fruits harvested by humans especially for the consumption or to produce wines and liquors. The American grapes (ca. 30 species) are recognised as an important resource because they show biotic and abiotic resistances. We analysed 3,885 genome-wide SNPs from 31 American Vitis species using the TreeMix software combined with the f3 and f4 tests. This approach allowed us to infer phylogenetic relationships and to explore the natural admixture among taxa. Our results confirmed the existence of all hybrid species recognised in literature (V. x champinii, V. x doaniana, V. x novae-angliae and V. x slavinii), identifying their most likely parent species and provided evidence of additional gene flows between distantly related species. We discuss our results to elucidate the origin of American wild grapes, demonstrating that admixture events have ancient origins. We observe that gene flows have involved taxa currently spread through the southern regions of North America. Consequently, we propose that glacial cycles could have triggered the contact between interfertile taxa promoting local hybridization events. We conclude by discussing the phylogenetic implications of our findings and showing that TreeMix can provide novel insights into the evolutionary history of grapes.